Review: Risiko Stunting pada Anak yang Tinggal di Area Pertambangan Emas Skala Kecil - Devi Puspita; Defi Patmasari; Sella Sella; Dwi Purbayanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Small Scale Gold Mining uses mercury to extract gold. Mercury exposure to children is associated with the risk of various health problems that can lead to stunting. This review was prepared with the aim of knowing the impact of mercury exposure on children living in the Small Scale Gold Mining area. The method used in the preparation of this narrative review is searching for information via the internet using google. Tracing results from various studies and electronic books stated that children living in ASGM areas are very vulnerable to mercury exposure either by inhalation by inhaling mercury vapor or ingestion by consuming food or drinks containing mercury. In addition, they are also very at risk of health problems such as malnutrition and infectious diseases, which are risk factors for stunting. Various risk factors that threaten the health of children living in ASGM areas can lead to stunting. However, there is still little research linking mercury exposure to stunting.